Corporate Governance and Marketing Performance: The Role of Customer Relations and Market Orientation - Hidayat, Muhammad (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2024)
The Company is very important to have the ability to distribute the strategies that have been set, especially in the implementation of corporate governance so that the Company is able to ensure that it can achieve predetermined goals. Purpose: the purpose of this study is to determine the extent to which the Company is able to distribute Corporate Governance strategies to improve marketing performance through consumer relationship management and marketing orientation. Research Design, Data, and Methodology: Data collection in this study was carried out by distributing questionnaires to 85 respondents who work as leaders in property industry companies in Makassar City. Result: corporate governance has no significant affect on marketing performance but corporate governance affect on customer relation and marketing orientation, customer relation affect on marketing performance, marketing orientation affect marketing performance. This research indicate that corporate governance affect marketing performance through customer relations and this research result also indicated that corporate governance affect marketing performance through marketing. Conclusion: D istribution of management policies to improve performance is very important to be considered by distribution management requires effective tools and this research shows that the distribution of the Company's strategy can be carried out through the concept of customer relationship management and marketing orientation.